From Jantzen to Andersen filtration via tilting equivalence - Kübel, Johannes (MATHEMATICA SCANDINAVICA, 2012)
The space of homomorphisms between a projective object and a Verma module in category O inherits an induced filtration from the Jantzen filtration on the Verma module. On the other hand there is the Andersen filtration on the space of homomorphisms between a Verma module and a tilting module. Arkhipov’s tilting functor, a contravariant self-equivalence of a certain subcategory of O, which maps projective to tilting modules induces an isomorphism of these kinds of Hom-spaces. We show that this equivalence identifies both filtrations.